Organic chemistry : for pharmacy students - Devínsky, Ferdinand, 1947-; Hudeček, Milan (Bratislava : Comenius University in Bratislava, 2010)
The book has thirteen chapters in total and is divided into two parts. The first part - two chapters in the extent of approximately half of the book - describes the foundations of organic chemistry and the theory of bonding in organic compounds, types of organic reactions and factors influencing these reactions, particularly stereochemical and electronic factors. This part includes also relations between structure and physical, physicochemical, constitutive, and spectral properties of organic molecules. In the chapter which describes the influence of stereochemistry on the biological effects of organic compounds we show examples of molecules whose different spatial arrangements affect their biological activity. The second part of the book offers the systematics of organic compounds structured in a classical way according to functional groups and reactions afforded by these groups or by molecules' secondary reactive sites induced thereby. Indeed, we are convinced that theoretical knowledge and factual information are part of all sciences including organic chemistry. This part has eight chapters including those on organometallic and heterocyclic compounds. The next three chapters describe natural substances (saccharides, terpenes, and steroids). The book is concluded with a relatively extensive index assisting in quick orientation in the text. The present book is the first Slovak textbook of organic chemistry for pharmacy students in an English edition written by Slovak authors.
Bibliogr. odkazy
Register
Keywords: chémia organická; štúdium farmácie; učebnica